2022
DOI: 10.3390/ijerph19063292
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Traffic-Related Air Pollution and the DNA Methylation in Cord Blood Cells: MOCEH Study

Abstract: Particulate matter with a diameter of ≤10 µm (PM10) and nitrogen dioxide (NO2) affect the DNA methylation in the fetus, but epigenetic studies regarding prenatal exposure to air pollution in Asia are lacking. Therefore, this study aimed to assess whether there is any association between the ambient concentrations of PM10 and NO2 and CpG methylation in the cord blood DNA by using a Korean birth cohort. The concentrations of the air pollutants were incorporated into the final LUR model by using the maternal addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Studies have shown that babies born with altered placental DNA methylation patterns are at risk for neurobehavioral abnormalities, cancer, and atopic dermatitis, among other diseases (Ghazi et al, 2021). Prenatal exposure to TRAP can also alter the methylation status of certain CpG sites, resulting in significant effects on biological events (Park et al, 2022).…”
Section: Mechanisms Of Pm‐induced Neurodevelopmental Disordersmentioning
confidence: 99%
“…Studies have shown that babies born with altered placental DNA methylation patterns are at risk for neurobehavioral abnormalities, cancer, and atopic dermatitis, among other diseases (Ghazi et al, 2021). Prenatal exposure to TRAP can also alter the methylation status of certain CpG sites, resulting in significant effects on biological events (Park et al, 2022).…”
Section: Mechanisms Of Pm‐induced Neurodevelopmental Disordersmentioning
confidence: 99%
“…DMRs initially detected in cord blood showed consistent exposure-related changed in DNA methylation in the placenta; however, those initially detected in the placenta showed no DNA methylation differences in cord blood—appearing to be tissue-specific [ 141 ]. In a Korean birth cohort [ 142 ], DNA methylation in association with PM 10 and NO 2 exposure were investigated; most significantly, a CpG site in the caspase 7 ( CASP7 ) gene could be associated both when addressing the entire pregnancy and during the second trimester. Furthermore, CpG sites related to WD repeat domain 93 ( WDR93 ) and family with sequence similarity 176 member A ( FAM176A ) could be associated with PM 10 and NO 2 exposure [ 142 ].…”
Section: The Role Of Air Pollution In the Pathogenesis Of Slementioning
confidence: 99%
“…In a Korean birth cohort [ 142 ], DNA methylation in association with PM 10 and NO 2 exposure were investigated; most significantly, a CpG site in the caspase 7 ( CASP7 ) gene could be associated both when addressing the entire pregnancy and during the second trimester. Furthermore, CpG sites related to WD repeat domain 93 ( WDR93 ) and family with sequence similarity 176 member A ( FAM176A ) could be associated with PM 10 and NO 2 exposure [ 142 ].…”
Section: The Role Of Air Pollution In the Pathogenesis Of Slementioning
confidence: 99%
“…The RNF39 protein is part of Major Histocompatibility Complex (MHC) class I, thus it is biologically plausible that altered RNF39 DNAm may be associated with changes in immune function 10 , including asthma. More recently, DNAm at CASP7 was associated with prenatal NO2 exposure across all trimesters in a Korean cohort 11 . The CASP7 gene is a critical mediator of mitochondria-induced apoptosis, thus this finding is consistent with previous observations of altered DNAm in mitochondrial oxidative stress pathways 8,12 .…”
Section: Introductionmentioning
confidence: 99%